2023
DOI: 10.1177/20406207221150305
|View full text |Cite
|
Sign up to set email alerts
|

Therapy for patients with chronic phase-chronic myeloid leukemia previously treated with ⩾2 tyrosine kinase inhibitors: a systematic literature review

Ehab Atallah,
Lovneet Saini,
Rodrigo Maegawa
et al.

Abstract: Background: ATP-competitive tyrosine kinase inhibitors (TKIs) are the current standard of care for patients with chronic phase-chronic myeloid leukemia (CP-CML) in the first-line and second-line (2 L) setting. Treatment after 2 L is not clearly established. Objective: The objective of this study was to summarize the available evidence to compare the efficacy and safety of interventions in the treatment of CP-CML patients who had received ⩾2 prior TKIs. Design: A systematic literature review was performed. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Overall, 17% of CML patients (n = 21) progressed to either AP-CML (n = 11) or BC-CML (n = 10). A study conducted and all approved TKIs in technologically advanced countries (2,3,13). Furthermore, there was a significant difference between chronic- and advanced-phase patients concerning male-to-female ratio, hemoglobin level, WBC count, and platelet count.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, 17% of CML patients (n = 21) progressed to either AP-CML (n = 11) or BC-CML (n = 10). A study conducted and all approved TKIs in technologically advanced countries (2,3,13). Furthermore, there was a significant difference between chronic- and advanced-phase patients concerning male-to-female ratio, hemoglobin level, WBC count, and platelet count.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in the United States reported CML progression occurred in 8% of the total patients, 35 out of 482 (7.3%) patients progressed to AP-CML and 7 BC-CML (19). These differences in rate of CML progression might be due to more advanced patient-care options like stem cell transplantation and all approved TKIs in technologically advanced countries (2,3,13). Furthermore, there was a significant difference between chronic-and advanced-phase patients concerning male-to-female ratio, hemoglobin level, WBC count, and platelet count.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CML is the first aberrant chromosome abnormality described in a malignancy, known as the Philadelphia (Ph+) chromosome (2). The presence of Philadelphia chromosome t (9:22), which is a chromosomal reciprocal translocation between Abelson murine leukaemia (ABL) on the long arm of chromosome 9 and breakpoint cluster region (BCR) on chromosome 22, is a defining feature of CML (2,3). As a result of BCR-ABL1 fusion oncoprotein (P210) and the constitutive activity of tyrosine kinase, hematopoietic stem cells (HSC) are expanded clonally and CML is induced (4,5).…”
Section: Introductionmentioning
confidence: 99%